THE INFLUENCE OF TRUST IN THE SUCCESS OF THE MAIN CHARACTER IN THE MOVIE BURNT BY MICHAEL KALESNIKO - Deddy Hidayat; Wahyuni (Prologue: Journal on Language and Literature, 2024)
This study aims to analyze the influence of trust in the main character's achievement in getting success in the movie Burnt by Michael Kalesniko. There are two objectives of this research. The first is to identify the types of beliefs in the movie. The second is how trust affects the success of the main character in the movie. The theory used in this study is Abraham Maslow's hierarchy of needs with the influence of trust as the key to success. Trust is used to see the achievement of the main character in passing each level of needs and its influence on the success contained in the film. The method used in this research is qualitative descriptive. The researcher found types of trust such as cognitive trust and affective trust. Each of these types is inseparable from how the main character meets each level of the hierarchy of needs. The trust that was initially based on the logic and ability of the main character grew stronger and gave rise to emotional trust that led to him succeeding in achieving success. The researcher concludes that trust is very influential to achieve success through the hierarchy of needs in the Burnt movie.